Altered gut fungal microbiota and associated mycotoxins in juvenile rat offspring induced by maternal immune activation with Poly I:C - Zhong, Fuchun; Zeng, Menglu; Chen, Huiyu; Lu, Yanfang; Cao, Zhenju; Xue, Fei; Yang, Shuangyan; Yang, Lirong; Yang, Xinyu; Lin, Wei; Shen, Anying; Su, Yueqing (Frontiers in Neuroscience, 2026)
BackgroundMaternal immune activation (MIA) is a risk factor for neurodevelopmental disorders (NDDs) in offspring. While MIA-induced changes in the gut bacterial communities of offspring and their metabolites have been linked to behavioral abnormalities, the effects of MIA on the gut fungal communities and their mycotoxin-associated metabolites in offspring remain poorly characterized.MethodsIn this study, MIA was modeled in pregnant rats through intraperitoneal injection of 5 mg/kg Poly I:C on gestational day 15. The model’s efficacy was validated using behavioral assessments, including the open-field test, elevated plus maze, and Morris water maze. Internal transcribed spacer (ITS) sequencing and untargeted metabolomics analysis were employed to detect the alterations of gut fungal microbiota and mycotoxin levels.ResultsPoly I:C-exposed offspring exhibited increased anxiety and cognitive deficits. Meanwhile, Poly I:C induces sex-related differences in gut fungal communities and mycotoxin levels in juvenile offspring rats. Several fungal genera and mycotoxins were significantly correlated with variations in anxiety-like behaviors and spatial learning performance.DiscussionOur findings suggest that MIA-induced behavioral deficits in offspring are accompanied by sex-specific disruptions in gut fungal composition and mycotoxin metabolism, which highlights the need for further intervention studies to establish causality and elucidate the underlying mechanisms of gut fungi and mycotoxins in NDDs.